The years of Monte dei Paschi's disengagement 2012–2019. (1st February 2023) - Ferri, Giovanni; Fiorito, Luca
Abstract: We review the critical phase of Economic Notes focusing on the years from 2012 to 2019 when the Journal suffered from the progressive disengagement by its founder, the Monte dei Paschi di Siena. The main reason for that gradual detachment is identified in the performance difficulties Monte was suffering from. Against the progressive fading away of the support provided by the Bank, the Journal entered a halo of the potential crisis itself. However, soon some measures were taken to allow Economic Notes to develop new and autonomous ways to project its own future. Specifically, we outline how the major changes in the structure of the Editorial Board were conducive to launching a new phase in which the Journal learned to rely more and more on low‐cost ways to gain visibility and attract quality submissions. That new strategy materialized through the widespread adoption of repeated Calls for Papers to generate the consequent Special Issues. The topics selected for the Calls for Papers were selected with a view at themes that were policy‐relevant and, whenever possible, not too far from the potential interest of Monte dei Paschi. We show that those Special Issues were functional to engineer a recovery in the Journal 's performance. It was essentially owing to that resumed good health and recovered resonance that when Monte finally abandoned it Economic Notes was by and large equipped for the new venture.